Canadaphis mordvilkoi, Kononova 1976 (Hemiptera: Sternorrhyncha: Canadaphididae)—redescription and neotype designation - Ogłaza, Bartosz; Perkovsky, Evgeny E.; Wegierek, Piotr (Zootaxa, 2022)
Here we present a redescription of an aphis species Canadaphis mordvilkoi Kononova, 1976 based on a recently found specimen originating from the same locality as holotype (Yantardakh (Kheta Formation), Taimyr Peninsula, Russia). The new specimen is far better preserved and many characters invisible and not mentioned in original description are available for our analysis. As a result, we were capable to indicate affinities with other species belonging to the Canadaphididae family. As the holotype is destroyed we decided to designate this specimen as a neotype. We also provide the photos of the type genus of this family for the first time.